SYMPTOM AND FUNCTIONAL TRAITS OF BRIEF MAJOR DEPRESSIVE EPISODES AND DISCRIMINATION OF BEREAVEMENT. Issue 2 (16th October 2015) - McCabe, Patrick J.; Christopher, Paul P.
Abstract : Background: Despite the removal of the bereavement exclusion from DSM‐5, clinicians may feel uncertain on how to proceed when caring for a patient who presents with depressive symptoms following the death of someone close. The ability to better distinguish, on a symptom and functional level, between patients who experience depression in the context of bereavement and those with nonbereavement‐related depression, could help guide clinical decision making. Method: Individual and clustered depressive symptom and impairment measures were used for modeling bereavement status within a nationally representative longitudinal cohort. Deviance, linear shrinkage factor, and bias‐corrected c ‐statistic were used for identifying a well‐calibrated and discriminating final model. Results: Of the 450 (1.2%) respondents with a single brief major depressive episode, 162 (38.4%) reported the episode as bereavement‐related. The bereaved were less likely to endorse worthlessness ( P < .001), social conflict ( P < .001), distress ( P < .001), thoughts of suicide ( P = .001), wanting to die ( P = .01), self‐medicating ( P = .01), and being withdrawn ( P = .04). In a multivariate model, the bereaved were more likely to have thoughts of their own death ( P = .003), guilt coupled with weight or appetite loss ( P = .013), and were less likely to report social conflict ( P < .001), worthlessness coupled with difficulty making decisions ( P < .001), thoughts of suicide ( P = .006), distress coupled with weight or appetite gain ( P = .022), and self‐medicating ( P = .045). Conclusions: Traits and trait combinations differentiate individuals who experience brief depressive episodes following the death of a loved one from other brief episodes. These differences can help guide clinical care of patients who present with depressive symptoms shortly after a loved one's death.